Multi‐angle spectroscopic extreme ultraviolet reflectometry for analysis of thin films and interfaces. Issue 3 (25th February 2015) - Danylyuk, Serhiy; Herbert, Stefan; Loosen, Peter; Lebert, Rainer; Schäfer, Anna; Schubert, Jürgen; Tryus, Maksym; Juschkin, Larissa
Abstract Modern nanotechnology is constantly raising demands to quality and purity of thin films and interlayer interfaces. As thicknesses of employed layers decrease to single nanometers, traditional characterization tools are no longer able to satisfy throughput, precision or non‐destructibility requirements. Extreme ultraviolet (EUV) and soft X‐ray reflectometry has not only demonstrated the ability to detect sub‐nm thickness variations but also was shown to be very sensitive to chemical composition changes. Since the laboratory radiation sources in this wavelength range often emit in a relatively broad spectral range, a spectroscopic EUV reflectometry has been developed with the added benefit of a rapid measuring time on the order of milliseconds to seconds. In this paper, the extension of the method to multi‐angle measurements will be presented. It allows to reduce a number of fit parameters in the analysis model, making the method suitable for complex samples of unknown composition. First experimental examples for Si‐based layer systems measured under grazing incidence angles between 2° and 15° will be demonstrated and discussed. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)